Personal positioning and location inferences (II) - Ng, Krystal Xing Yi. (2012)
In the recent years, there has been increased usage of phones equipped with GPS functions. This trend has brought about the scenario where the cellphone user is able to generate GPS records continuously. From this continuous data, new types of information such as the cellphone user’s travelling patterns can be obtained. By making use of the individual’s travelling pattern over time, there is the likelihood of carrying out predictions of the future locations that the individual may travel to.